SLANG WORD IN TINY MEAT GANG PODCAST: A SOCIOLINGUISTIC ANALYSIS - Oktavia Saputri; Yenti; Lestari, Putri Ayu (English Language, Linguistics, Literature, And Education Journal, 2025)
Slang is a language uses in non-formal situations, which has no meaning according to its literal meaning, which is commonly uses among young people as a form of defiance or rejection from formal language. The purposes of this research are to describe the types of slang and explain the functions of slang used in Tiny Meat Gang Podast. The approach used in this reseach is a sociolinguistic approach with a qualitative descriptive method. This research used the slang theory of Allan and Burridge to describe the types of slang and the functions of slang. The researcher analyzed the data source by analyzing conversational dialogue from podcasts through YouTube transcripts. The results show that 1) There are five types of slang found in this Tiny Meat Gang Podcast, namely Fresh and Creative, Flippant, Imitative, Acronym, and Clipping, and all five were found in this research. 2) There are seven functions of slang according to Allan and Burridge, namely to Address, to Humiliate, to Initiate Relaxed Conversation, to Form Intimate Atmosphere, to Express Impression, to Reveal Anger, and to Show Intimacy. However, only five functions of this research were found, namely to Address, to Humiliate, to Initiate Relaxed Conversation, to Express Impression, and to Reveal Anger. Through this slang word analysis, it is hopes that slang will continue to use without shifting the official and formal language, however, only for the non-formal scope, so that closer social ties with others will be created.